Cerebrovascular response to maternal hyperoxygenation in fetuses with hypoplastic left heart syndrome depends on gestational age and baseline cerebrovascular resistance. (3rd September 2018) - Szwast, A.; Putt, M.; Gaynor, J. W.; Licht, D. J.; Rychik, J.
ABSTRACT: Objectives: Compared with normal fetuses, fetuses with hypoplastic left heart syndrome (HLHS) have smaller brain volumes and are at higher risk of brain injury, possibly due to diminished cerebral blood flow and oxygen content. By increasing cerebral oxygen delivery, maternal hyperoxygenation (MH) might improve brain development and reduce the risk of brain injury in these fetuses. This study investigated whether gestational age and baseline cerebrovascular resistance affect the response to MH in fetuses with HLHS. Methods: The study population comprised 43 fetuses with HLHS or HLHS variant referred for fetal echocardiography between January 2004 and September 2008. Middle cerebral artery (MCA) pulsatility index (PI), a surrogate measure of cerebrovascular resistance, was assessed between 20 and 41 weeks' gestation at baseline in room air (RA) and after 10 min of MH. Z ‐scores of MCA‐PI were generated. A mixed‐effects model was used to determine whether change in MCA‐PI depends upon gestational age and baseline MCA‐PI. Results: In RA and following MH, MCA‐PI demonstrated a curvilinear relationship with gestational age in fetuses with HLHS, peaking at around 28 weeks and then falling more steeply near term. MCA‐PI Z ‐score declined in a linear manner, such that it was 1.4 SD below that in normal fetuses at 38 weeks. Increase in MCA‐PI Z ‐score after MH was first seen at ≥ 28 weeks. A baseline MCA‐PI Z ‐score ≤ −0.96 was predictive of an increase in cerebrovascular resistance in response to MH. Conclusion: In fetuses with HLHS, MCA‐PI first increases in response to MH at ≥ 28 weeks' gestation. A baseline MCA‐PI Z ‐score ≤ −0.96 predicts an increase in cerebrovascular resistance in response to MH. These results may have implications for clinical trials utilizing MH as a neuroprotective agent. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.